“SOSIOLOGI SASTRA PENGANTAR RINGKAS” COVER DESIGN BY 369 IN SCHLEIERMACHER'S HERMENEUTIC PERSPECTIVE - Rahardjo, Moelyono (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This study aims to investigate the process of role-changing taken by the author, who designs his book covers using the pseudonym “369”. The author's knowledge and experiences in self-publishing showed how his process relates to what is now known as visual communication design democratization. Schleiermacher's hermeneutic perspective is used to comprehend the process of the roles-changing and thoughts of the designer/author in exploring knowledge of visual communication design, which may be understood through other perspectives held by 369. By using an empathetic and divinatory approach, as Schleiermacher suggested, this study finds the transtextual relationship between the book cover design as text and the text of the book's contents, as well as other texts from the same author. This transtextual relationship becomes a way to re-reflect on the democratization of visual communication design.